Silver Wedding Anniversary of Our Constitution: Ticket to the future, an educational project commemorating 25 years of our Constitution - Atance Ibar, Javier (Pulso. Revista de educación, 2004)
The project: Spanish Constitution: Javier Atance Ibar, Director, Itziar de la Orden Estévez, Head of Studies, and María Pilar de la Fuente, Secretary, together comprising the Management Team of the Virgen de la Paz School of Alovera (Guadalajara), were among the victors of the National Contest on Educational Innovation Projects. This competition aimed to explore, promote, and engage students in the contents and constitutional values at Infant and Primary levels, and was organised by the Spanish Ministries of Education and Culture and Sports (MECD) in honour of the 25th anniversary of the Spanish Constitution. Their winning project was titled "Banknote of the Future." Within the project, there is a diverse assortment of activities and recommendations intended to transform the dense subject matter of our Constitution into an enjoyable, rich, and fulfilling learning experience. The goal is to foster values of coexistence, respect, and solidarity, which we aim to summarise here.